Listener perception of appropriateness of L1 and L2 refusals in English - Kostromitina, Maria; Miao, Yongzhi (Studies in Second Language Learning and Teaching, 2024)
English has become an international language (EIL) as speakers around the world use it as a universal means of communication. Accordingly, scholars have investigated different aspects of EIL affecting communicative success. Speech scholars have been interested in speech constructs like accentedness, comprehensibility, and acceptability (e.g., Kang et al., 2023). On the other hand, pragmatic researchers have examined lexico-grammatical features of EIL that contribute to first language (L1) English listeners’ perceptions of appropriateness in speech acts (e.g., Taguchi, 2006). However, little is known about: a) how appropriateness is perceived by users of EIL of diverse L1s and b) how those appropriateness perceptions are related to lexico-grammatical and phonological features. Therefore, the present study had 184 listeners (L1 = English, Spanish, Chinese, and Indian languages) evaluate 40 speech acts performed by 20 speakers (L1 English and Chinese, 50% each) in terms of appropriateness on a 9-point numerical scale. Results from linear mixed-effects regressions suggested that: a) listener L1 did not contribute to listener ratings and b) speakers’ rhythm and lexico-grammatical features (i.e., use of different pragmatic strategies) significantly contributed to listener appropriateness ratings. The findings provide empirical evidence to support the phonology-pragmatics link in appropriateness perceptions and offer implications regarding the operationalization of English interactional appropriateness.